The Influence of Application of the Rasul Sunnah on Vital Signs of Lung Cancer Patients Undergoing Chemotherapy - Putri, Diyanah Syolihan Rinjani; Wulanningrum, Dian Nur; Suryandari, Dewi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Lung cancer patients receive chemotherapy treatment. One of the effects of chemotherapy is that it can cause a physiological response to changes in vital signs. Applying the Sunnah of the Apostle can relax and influence vital signs in lung cancer patients undergoing chemotherapy. Objective: to determine the effect of applying the Sunnah of the Apostle on the vital signs of lung cancer patients undergoing chemotherapy. Method: Quasi experimental with one group pre test – post test with control design, sample of 42 lung cancer respondents. Assessment of vital signs using a Spygmomamometer, stopwatch and thermometer. Data were analyzed using the Wilcoxon test. Results: The Wilcoxon test results obtained a p-value of 0.000 (p-value < 0.05). Conclusions: there is an influence of the application of the Prophet's Sunnah on the vital signs of lung cancer patients undergoing chemotherapy.